A case series of dermatomyositis following SARS-CoV-2 vaccination - Chan, Airiss R.; Cohen Tervaert, Jan Willem; Redmond, Desiree; Yacyshyn, Elaine; Ferrara, Giovanni; Hwang, Peter M.; Osman, Mohamed; Gniadecki, Robert (Frontiers in Medicine, 2022)
Background/Objective The most significant adverse events following SARS-CoV-2 vaccination are myocarditis and pericarditis. Myositis and dermatomyositis have been reported following SARS-CoV-2 infection, but vaccine-induced dermatomyositis (DM) has not been reported. Our case series aimed to characterize new onset dermatomyositis or disease-related flares following SARS-CoV-2 vaccination. Materials and methods A total of 53 patients from our institution with a new or pre-existing diagnosis of DM were recruited and consented. Phone interviews were conducted to obtain vaccination status and symptoms following vaccination. Electronic medical records were reviewed to extract age, sex, autoantibody profiles, comorbidities, immunomodulatory therapies, creatine kinase (CK) values, and SARS-CoV-2 vaccination dates from the provincial vaccination registry. For patients who reported disease flares, records were reviewed for the onset and nature of symptoms, extent of organ involvement and changes in immunomodulation. Results On average, patients received 2.62 vaccine doses (range 1–3 doses). A total of 3 of 51 patients (5.88%) experienced dermatomyositis symptoms following vaccination. Two patients were newly diagnosed with dermatomyositis, one requiring hospitalization. Reported symptom onset following vaccination ranged from 1 to 30 days. Of note, all of these patients had normal CK values, even though there was muscle biopsy-confirmed myositis in one patient. Eight patients in the cohort (15.1%) had asymptomatic CK elevation (<1.5 X ULN). Conclusion New onset dermatomyositis or flare up of pre-existing dermatomyositis may be a rare complication in SARS-CoV-2 vaccination although no studies can support a true correlation. Several pathophysiologic mechanisms are proposed.